2019
DOI: 10.2174/1567202616666190129153409
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cognition, Depression and Quality of Life after Carotid Stenosis Treatment

Abstract: Background: Although several studies have evaluated the change of cognitive performance after severe carotid artery stenosis, the results still remain elusive. The objective of this study was to assess changes in cognitive function, depressive symptoms and Health Related Quality of Life (HRQoL) after carotid stenosis revascularisation and Best Medical Treatment (BMT).Methods: Study involved 213 patients with ≥70% carotid stenosis who underwent assessment of cognitive function using Montreal Cognitive Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
2
8
0
4
Order By: Relevance
“…There were also differences in postoperative changes in mood between the patient groups. In accordance with previous findings ( 60 ) we found no changes in depressive symptoms after CEA. In contrast, there were changes in mood after CABG in the present study: depressive symptoms were significantly higher in the acute phase and reduced in the stable phase compared with baseline.…”
Section: Discussionsupporting
confidence: 93%
“…There were also differences in postoperative changes in mood between the patient groups. In accordance with previous findings ( 60 ) we found no changes in depressive symptoms after CEA. In contrast, there were changes in mood after CABG in the present study: depressive symptoms were significantly higher in the acute phase and reduced in the stable phase compared with baseline.…”
Section: Discussionsupporting
confidence: 93%
“…A similar position was taken by Kim et al, who observed a significant improvement in memory and executive functions in patients after vascular interventions [41]. Other researchers recorded an increase in MoCA scores 6 and 12 months after CEA and 12 months after CAS, and no changes in the pharmacologically treated group [42]. In another study, improvement after CAS occurred in episodic, encoded, and working memory, as well as executive functions, while improvement after CEA affected episodic and encoded memory, as well as delayed recall.…”
Section: Comparison Of Cas and Ceasupporting
confidence: 58%
“…As mentioned earlier, a review of the available literature suggests that carotid revascularization procedures improve cognitive performance, with no significant differences depending on the method [37,[39][40][41][42][43][44][45]. This view is also supported by Brajesh K. et al However, when comparing the results obtained by specific individuals in the study conducted by these authors, it is found that the post-CEA group performed better on psychomotor tests, while the post-CAS group performed better on memory and concentration tests.…”
Section: Comparison Of Cas and Ceamentioning
confidence: 90%
“…Other researchers also confirmed the significant improvement of executive functions and memory after vascular interventions in patients with carotid atherosclerosis [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 68%